2019
DOI: 10.1111/ggi.13614
|View full text |Cite
|
Sign up to set email alerts
|

Subiculum volumes associated with memory function in the oldest‐old individuals aged 95 years and older

Abstract: Aim Few cohort studies targeting the oldest‐old individuals have been carried out. The subiculum in the hippocampus is thought to be related to memory function, and atrophy of this structure might result in the conversion from amnestic mild cognitive impairment to Alzheimer's disease. Thus, we sought to examine the relationship between subiculum volumes and memory function in individuals aged ≥95 years, using a novel cognitive examination called the Addenbrooke's Cognitive Examination III (ACE‐III) and an adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(54 reference statements)
0
5
0
1
Order By: Relevance
“…A combination of low hippocampal and high WMH volume was associated with the fastest decline on all cognitive tests [35]. Another recent study in the oldest-old found associations between volumes of hippocampal subfields and memory scores in a cohort of participants aged 95 or older (N = 10, mean age 97.6 years) [36].…”
Section: Anatomical Mri In Relation To Cognitionmentioning
confidence: 88%
See 1 more Smart Citation
“…A combination of low hippocampal and high WMH volume was associated with the fastest decline on all cognitive tests [35]. Another recent study in the oldest-old found associations between volumes of hippocampal subfields and memory scores in a cohort of participants aged 95 or older (N = 10, mean age 97.6 years) [36].…”
Section: Anatomical Mri In Relation To Cognitionmentioning
confidence: 88%
“…• Lower hippocampal volumes were associated with a faster rate of decline in global cognition along with lower test scores in the following domains: global cognition, memory, processing speed, and executive functioning [35]. Smaller subiculum volumes were associated with lower memory scores on the ACE-III [36].…”
Section: Studiesmentioning
confidence: 94%
“…Slower rates of memory decline have also been associated with larger baseline whole brain volume across the older adult lifespan (Carmichael et al, 2012). Cross-sectional studies similarly report that oldest-old adults with larger hippocampus volumes have better episodic memory performance (Eguchi et al, 2019) and faster processing speeds (Legdeur et al, 2020;Pelkmans et al, 2021), comparable to what has been reported in younger-old adults (Carr et al, 2017;Gorbach et al, 2017;O'Shea et al, 2016).…”
Section: Neurocognitive Aging In the Oldest-oldmentioning
confidence: 67%
“…Slower rates of memory decline have also been associated with larger baseline whole brain volume across the older adult lifespan (Carmichael et al, 2012). Cross-sectional studies similarly report that oldest-old adults with larger hippocampus volumes have better episodic memory performance (Eguchi et al, 2019) and faster processing speeds (Legdeur et al, 2020;Pelkmans et al, 2021), comparable to what has been reported in younger-old adults (Carr et al, 2017;Gorbach et al, 2017;O'Shea et al, 2016). Larger volume of the hippocampus was also found to predict better memory performance in individuals across the lifespan (ages 4-93 years; Langnes et al, 2020).…”
Section: Neurocognitive Aging In the Oldest-oldmentioning
confidence: 96%